Fatores intervenientes na função cognitiva de pacientes hipertensos em uma região do Baixo Amazonas - Bahia, Mariane de Araujo (Brasil, 2023)
Systemic arterial hypertension (SAH) is associated with several causes of Mortality. Patients with this disease have a cognitive decline. Physical exercise has been an important strategy to improve the deleterious effects of the disease. In other clinical populations, low levels of physical activity are associated with declining cognitive functions. However, no study has sought to investigate this association in hypertensive patients. The aim of the present study was to identify the correlation between the level of physical activity and cognitive capacity in patients with SAH. In this observational, cross-sectional study, 22 patients diagnosed with systemic arterial hypertension participated, recruited through advertising on posters, social media, radio and television. Demographic data were obtained through the application of a questionnaire. The level of physical activity (independent variable) was assessed using the International Physical Activity Questionnaire (IPAQ-short version). For data analysis, a normality test was performed using the Shapiro-Wilk test, descriptive measures were presented with mean values and standard deviation, and subsequently the Chi-square test was applied for levels of PA and cognitive function, with a criterion of statistical significance , P<0.05. There was no significant correlation between the level of physical activity and cognitive function p=0.727. Thus, these results suggest that the level of physical activity does not seem to influence cognitive function.